Hiccups and multiple sclerosis - Rawiphan Witoonpanich (2018)
Hiccups is a rare and unfamiliar presenting symptom of multiple sclerosis. Patients admitted to Ramathibodi Hospital from 1969 to 1992 who had a clinical diagnosis of multiple sclerosis were reviewed. The presenting symptoms and neurological signs were analysed. The clinical features and course of the disease of cases who initially presented with intractable hiccups were studied in detail. There were 4 cases out of a total of 47 cases (8.5%) who presented with hiccups. These patients all had relapse and remission and two of them had a rather fulminant course of illness. Therefore, multiple sclerosis should be seriously considered as a possible cause of intractable hiccups. It may be of benign or malignant form. In the latter, the patients may develop quadriparesis within hours or days and respiratory failure may ensue. They usually respond well to high dose intravenous corticosteroids especially pulse methylprednisolone.